2021
DOI: 10.3390/s21020578
|View full text |Cite
|
Sign up to set email alerts
|

A Soft Exoskeleton Glove for Hand Bilateral Training via Surface EMG

Abstract: Traditional rigid exoskeletons can be challenging to the comfort of wearers and can have large pressure, which can even alter natural hand motion patterns. In this paper, we propose a low-cost soft exoskeleton glove (SExoG) system driven by surface electromyography (sEMG) signals from non-paretic hand for bilateral training. A customization method of geometrical parameters of soft actuators was presented, and their structure was redesigned. Then, the corresponding pressure values of air-pump to generate differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Such exoskeletons, therefore, limit the natural joint movements of hands and even restrain the mobility of the user due to complicated electric tethering and the substantial weight of the exoskeletons. In this regard, recent studies demonstrate hand exoskeletons with minimal and lightweight designs that do not interfere with hand movements [58,92,97,98,100,[106][107][108].…”
Section: Hand Exoskeletonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such exoskeletons, therefore, limit the natural joint movements of hands and even restrain the mobility of the user due to complicated electric tethering and the substantial weight of the exoskeletons. In this regard, recent studies demonstrate hand exoskeletons with minimal and lightweight designs that do not interfere with hand movements [58,92,97,98,100,[106][107][108].…”
Section: Hand Exoskeletonsmentioning
confidence: 99%
“…Although the incorporation of the deep-learning algorithm into the whole system enables the active actuation in accordance with the user's intent, a very few studies incorporated the learning algorithm to make the system much easier to use [92,97,108], in such a way that all the user needs to do is to make a pre-trained movement to for the exoskeleton to augment the strength and control for the movement. One of these previous studies demonstrated the deeplearned, soft exoskeleton for the hand motor function rehabilitation purpose as in figure 8(c).…”
Section: Hand Exoskeletonsmentioning
confidence: 99%
“…Control type Accuracy Delay (2) [53] Point-in-Polygon (PIP) (3 predefined gestures) Accuracy: 0.944 - [57] EMG-driven (neural network to determine force) Force error = 20.7 % - [68] Threshold algorithm -- [69] Linear Bayes classifier (6 predefined gestures) Accuracy (1) : 98.1±4.9% Yes [70] Classification algorithm (6 predefines gestures) Accuracy: 86.38 % Yes [71] EMG-based intent inference method -- [72] Neural network -- [73] Forest classifier (3 predefined gestures) Accuracy: 77.9-85.2 % - [74] Neural Network (4 predefined gestures) Accuracy: 98.7±0.53 - (1) Accuracy for neurologically intact subjects. (2) Whether delay analysis of the system is carried out.…”
Section: Refmentioning
confidence: 99%
“…After a stroke, paretic limbs usually suffer muscle spasticity and weakness, mostly in the first weeks after the episode [59]. Usually, flexors have more MyoArmband (Thalmic Labs) Not specified Inference method no no [72] Trigno wireless EMG system (Delsys) Not specified Neural network no no [73] MyoArmband (Thalmic Labs) Not specified Forest classifier yes no [74] Cyton (OpenBCI) PC Neural network yes no (1) Whether information about accuracy of the EMG control is provided. (2) Whether delay analysis of the system is carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Trabajos previos relacionados [1], [2], [3], [10], [12], [13], [15], [20] presentaban dos inconvenientes: alto coste del sistema debido a la utilización de sistemas de adquisición de señales EMG comerciales (solo [15] utiliza sistemas de bajo coste, considerados como aquellos que cuesta menos de 150 €) y ejecución del procesamiento de las señales y del control en un ordenador, lo que puede incrementar el tiempo de latencia total del sistema. Teniendo en cuenta lo anteriormente expuesto, el sistema electrónico embebido desarrollado se ha diseñado para reducir el coste y el tiempo de latencia del sistema al máximo.…”
Section: Sistema Electrónicounclassified